Endoscopic Treatment of Refractory Gastroesohageal Reflux Disease - Kim, Won Hee (The Korean Society of Gastrointestinal Endoscopy, 2013)
Though efficient acid suppression with proton pump inhibitors (PPIs) remains the mainstay of treatment of gastroesophageal reflux disease (GERD), some of the patients showed refractory response to PPIs, necessitating further intervention. After increasing dose of PPIs and other kinds of pharmacological intervention adopting prokinetics or others, variable endoscopic treatments are introduced for the treatment of these refractory cases. The detailed introduction regarding endoscopic treatment for GERD is forwarded in this review article. Implantation of reabsorbable or synthetic materials in the distal esophagus was tried in vain and is expelled from the market due to limited efficacy and serious complication. Radiofrequency energy delivery (Stretta) and transoral incisionless fundoplication (EsophyX) are actively tried currently.